Tapering recommendations for long distance running leading into a major competition - Sarkies, R. (Journal of Australian Strength and Conditioning, 2016)
One of the main reasons elite athletes train and compete in their chosen sport is to produce the best performance possible at certain times of their career. Adjusting their training schedule leading into very important competitions is known to elicit such a performance if done correctly. This is known as tapering or peaking. This paper examined the literature and research on tapering methods plus 5 specific examples from Australian athletes at national or international level. Coaches of these 5 athletes were asked to provide training details of the 4 weeks leading into a major national or international competition. A range of different methods were seen, indicating that each athlete must be treated as an individual and the coach be specific to their situation when structuring the taper schedule. Many factors must be taken into account. It is recommended to conduct a taper over 1-4 weeks. During this period reduce running volume by 40-80%, maintain and/or increase intensity, and reduce frequency of sessions by 20-50%. For 5km and 10km the most difficult session should be conducted 5-10 days before competition, and up to 30 days for the Marathon.